134 Effect of a single short electrostimulation session of the fibularis muscles on dynamic postural stability and evertor muscles strength. (3rd March 2020) - Fourchet, François; Ganchine, Artiom; Seurot, Antoine; Coroller, Nicolas Le; Servant, Guillaume; Gojanovic, Boris
Abstract : Background: The fibularis muscles are key elements of the ankle evertor group (evertors). The weakness of evertors is one of the main cause of ankle sprains. Electrostimulation training can increase the maximum voluntary force of contraction by neural adaptation to a healthy skeletal muscle. Objective: To assess whether a single electrostimulation session of the fibularis muscles could impact dynamic postural stability and evertor strength. Design: Single-blind randomised controlled trial. Setting: Motion analysis laboratory in a hospital facility. Patients (or Participants): Sixteen healthy male and female volunteers, randomly assigned to an experimental (EXP, n=8) or control (Control, n=8) group. Interventions (or assessment of risk factors): Participants in EXP received a single electrostimulation strengthening session for 3 minutes on the dominant side (DOM) fibularis muscles. Control participants received a sham electrostimulation on DOM with similar modalities. Main outcome measurements: Dynamic postural balance was assessed on DOM and non-dominant (NDOM) limbs using the modified Star Excursion Balance Test (SEBT). A composite score (CS in%) was calculated. Evertor strength (in N) was assessed with three maximal isometric voluntary contractions on an isokinetic dynamometer. Results: EXP displayed a significant increase in SEBT-CS on DOM (97.7±5.9% vs 96.1±7.4%, p<0.05) and NDOM (97.6±7.2% vs 95.6±7.4%, p<0.01), while these parameters did not change in Control. EXP also displayed a significant increase in Evertors isometric strength on DOM (25.0±7.0N vs 23.1±6.8N, p<0.05) and NDOM (26.8±6.0N vs 22.9±5.2N, p<0.001). In Control, evertor isometric strength increased on DOM (24.9±7.4N vs 23.1±6.8N, p<0.01), but remained unchanged on NDOM. Conclusions: A short single fibularis elecrostimulation session on one leg appeared to improve dynamic postural stability on both sides and evertors strength on the stimulated side only, suggesting a global post-activation potentiation effect of this intervention and a possible additional mirror effect on dynamic postural stability. These findings may be of interest for preventing ankle sprain.